2014
DOI: 10.1007/s00213-014-3483-8
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric differences in the anterior cingulate cortex prospectively predict alcohol-related problems in adolescence

Abstract: These findings indicate that individual differences in the structural morphology of the anterior cingulate, a region implicated in affective processes, self-control, and drug addiction, predict later alcohol-related problems. Although this finding remained significant after controlling for other substance use and psychopathology, future research is required to test its specificity for alcohol use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 77 publications
3
63
1
1
Order By: Relevance
“…In support of this, a recent longitudinal study reported that smaller amygdala volumes were associated with higher self-reported negative affectivity at baseline and more subsequent alcohol-related problems (Cheetham et al, 2014). Smaller amygdala volumes may contribute to alcoholism risk via increased externalizing symptoms, such as impulsivity (Benegal et al, 2007;Tessner and Hill, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…In support of this, a recent longitudinal study reported that smaller amygdala volumes were associated with higher self-reported negative affectivity at baseline and more subsequent alcohol-related problems (Cheetham et al, 2014). Smaller amygdala volumes may contribute to alcoholism risk via increased externalizing symptoms, such as impulsivity (Benegal et al, 2007;Tessner and Hill, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…To date, this literature has identified a range of predictors of early substance use and SUD that are also associated with the development of mental health disorders, including (but not limited to) individual variation in temperament (e.g. [4]), externalizing symptoms (e.g. [5]) and family history of substance use and other mental disorders (e.g.…”
mentioning
confidence: 99%
“…[6]). However, these studies have often been unable to examine trajectories associated with the early use of specific substances or the development of distinct SUDs [4,5], and have often relied upon samples recruited from families with a history of substance dependence [6]. As such, there are limited data on risk factors for the development of specific SUD/mental health comorbidity in nonclinical samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the recent article by Cheetham et al (2014) examining brain structure of adolescents and the potential relationship with developing problematic drinking behavior. The data seem to indicate that anterior cingulate cortex (ACC) volume predicts the development of alcohol-related problems.…”
mentioning
confidence: 99%